Vulnerabilidade natural à contaminação da água subterrânea em área ocupada por aterro sanitário em Seberi - RS - Borba, Willian Fernando de (2016)
The issue involving the proper management of municipal solid waste is still a serious problem that affects mainly developing countries, just as Brazil. Only in 2010, with the implementation of the National Solid Waste Policy from the Federal Law No 12.305, this issue began to gain traction in the social and economic environment. In this law one of the proposals is the removal and recovery inappropriate sites for the disposal of municipal waste. The adverse consequences of waste disposal involve two fundamental issues, regarding the contaminants migration and another that deals with the sites stability used for their disposal. Therefore, this study aimed to analyze the support of the geological environment for the operation of a landfill. The enterprise is a public consortium, licensed by the responsible environmental agency, and is located in the northwest region of the State of Rio Grande do Sul, in the Volcanic Plateau Province of Serra Geral. Thus, there were performed studies of the soil, involving physical, chemical and geotechnical parameters. Regarding the groundwater quality parameters, there were evaluated the water of four active monitoring wells and one of supply, besides the water level variation in a period exceeding hydrologic year. The soil was classified as very clayey, with average clay content of 86 %, and predominance of micropores, common in clayey soils. The saturated hydraulic conductivity of the not compacted soil presented values in the order of 10-4 cm.s-1. Geotechnical parameters were within the described by current standards, with mean values of liquid limit, plastic and shrinkage of 68,83, 41,73 and 28,94 %, respectively, being the soil classified like highly plastic. In relation to the clay fraction, its colloidal activity was classified with low activity, with the presence of non-expansive kaolinite 1:1. The soil presented low values of cation exchange capacity, it was also identified that only copper and chrome elements were above proposed by State law. In relation to the qualitative parameters of groundwater, was identified changes in the concentration of coliforms, nitrate and ammoniacal nitrogen, in some of the samples. In the quantitative matter the area showed a wide variation in water levels, and the rainfall showed significant correlation at 5 % with the water level in three monitoring wells (01, 03 and 05), situated in different positions in the landscape. Regarding the aquifer vulnerability to contamination, the area was classified as a low vulnerability area. Thus, it is concluded that the shallow aquifer in the study area showed variable behavior, in local and regional scales. Changes were identified in the quality of the groundwater in some samples in different periods, between 2007 and 2015.